Unusual Complication following a Myomectomy: Colic Migration of a Forgotten Abdominal Swab - Tchangai, Boyodi (Case Rep Surg, 2017)
Surgical sponges are the most common retained foreign bodies following surgery. The morbidity of this condition is illustrated herein with the case of a 36-year-old female patient with a history of myomectomy 5 months before her admission into our unit for enterocutaneous fistula. Although imaging and etiological investigations were made, diagnosis was carried out only by laparotomy. The foreign body found was an abdominal swab that migrated from abdominal cavity to the colon causing several intestinal injuries. The lack of specific clinical signs and the death of the patient raise the necessity of preventing these complications that involve the surgeon liability.